Editorial Notes: Decentering Islamic Studies - Hasan, Noorhaidi (Islamic Studies Review, 2022)
After Orientalism, a landmark work edited by Francois Pouilion and Jean-Claude Vatin, was published in 2014 in the Leiden Studies in Islam and Society series in collaboration with renowned publisher, Brill. The work, featuring dozens of leading scholars including Francois Pouilion, Jean-Claude Vatin, Robert Irwin, Leon Buskens, Baudouin Dupret, Zakaria Rhani, Jessica Marglin, Oliver Herrenschmidt, Edhem Eldem, Emmanuel Szurek, Stephane Dudoignon and Elisabeth Alles, is aimed at shifting the focus of Islamic studies from the 'centre' to the 'periphery', by raising new issues through innovative perspectives.